2014
DOI: 10.1021/la501068e
|View full text |Cite
|
Sign up to set email alerts
|

Donnan Potentials in Aqueous Phase-Separated Polymer Mixtures

Abstract: A promising approach to texturize water is by the addition of mutually incompatible polymers, leading to phase separation. Here, we demonstrate that the phase stability of aqueous polymer solutions is affected not only by chemical differences between the polymers but also by their electric charge. Direct electrochemical measurements are performed of the electric potential difference between two coexisting phases in aqueous solutions of the charged protein fish gelatin (nongelling) and the uncharged polysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 38 publications
3
51
0
Order By: Relevance
“…With increasing TLL and polymer molecular weight, cell adsorption at the interface increased. Although this theory of a “charge‐dependent partitioning” is supported by the findings of different groups, doubts have been expressed about the existence of an electrochemical potential in ATPS . Despite the debate about the existence of Donnan potentials and their significance in cell partitioning, the data presented here show a clear influence of sodium phosphate on cell partitioning and the resolution of different cell types.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…With increasing TLL and polymer molecular weight, cell adsorption at the interface increased. Although this theory of a “charge‐dependent partitioning” is supported by the findings of different groups, doubts have been expressed about the existence of an electrochemical potential in ATPS . Despite the debate about the existence of Donnan potentials and their significance in cell partitioning, the data presented here show a clear influence of sodium phosphate on cell partitioning and the resolution of different cell types.…”
Section: Discussionsupporting
confidence: 57%
“…It has been shown that salts with polyvalent anions, e.g., phosphate have a higher affinity for the dextran‐rich bottom phase that the PEG‐rich top phase, while salts of halides, for example, NaCl, partition almost equally between the phases . It was further proposed that unequal partitioning of a salt results in the generation of an interfacial electrostatic potential difference (Donnan potential), and molecules and particles partition in such ATPS according to their surface charge . In PEG‐dextran, ATPS containing phosphate with moderate interfacial tensions cells can, therefore, be separated based on surface charge differences (“charge‐dependent partitioning”).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed accounts on sample preparation, Donnan potential measurements, and the analysis of the composition of the coexisting phases, are given in ref 9.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…From the optical rotation at various wavelengths and the dilution factors, the mass fractions of dextran and gelatin in the original sample were obtained for each phase. 9 The measurement principle is based on the fact that both polymers are optically active and that their optical rotary dispersionthe dependence of optical rotation on wavelengthis different. As mentioned in the Theory section, for a given sample, the tie-line length is defined as…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Proteins have been demonstrated that, along with polysaccharides, can be used in phase-separated mixtures to texturize water (Vis et al, 2014). Such cases have been studied in detail in model aqueous systems containing two biopolymers since the late seventies.…”
mentioning
confidence: 99%